2020
DOI: 10.1002/jcla.23055
|View full text |Cite
|
Sign up to set email alerts
|

Identification of A‐kinase interacting protein 1 as a potential biomarker for risk and prognosis of acute myeloid leukemia

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractBackground: This study aimed to investigate the correlation of A-kinase interacting protein 1 (AKIP1) expression with disease risk, clinical characteristics, and prognosis of acute myeloid leukemia (AML).Methods: 291 de novo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Finally, 19 studies with 19 cohorts were included in this meta-analysis. The 19 cohorts, with a total of 3979 patients, were recruited throughout China, and patients were diagnosed with multiple types of cancer, that is tongue squamous cell carcinoma, [8] papillary thyroid carcinoma, [17] acute myeloid leukemia, [20,28] multiple myeloma, [19] prostate cancer, [25] cervical cancer, [27] clear cell renal cell carcinoma, [11] NSCLC, [16,21,26] gastric cancer, [15,18] hepatocellular carcinoma, [12,24,29] colorectal cancer, [22] breast cancer, [23] and epithelial ovarian cancer. [30] The sample sizes ranged from 50 to 490.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, 19 studies with 19 cohorts were included in this meta-analysis. The 19 cohorts, with a total of 3979 patients, were recruited throughout China, and patients were diagnosed with multiple types of cancer, that is tongue squamous cell carcinoma, [8] papillary thyroid carcinoma, [17] acute myeloid leukemia, [20,28] multiple myeloma, [19] prostate cancer, [25] cervical cancer, [27] clear cell renal cell carcinoma, [11] NSCLC, [16,21,26] gastric cancer, [15,18] hepatocellular carcinoma, [12,24,29] colorectal cancer, [22] breast cancer, [23] and epithelial ovarian cancer. [30] The sample sizes ranged from 50 to 490.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Moreover, AKIP1 is overexpressed in various cancers [12,15–23] . Thus, clinical studies have shown that AKIP1 overexpression is associated with poorer survival in a variety of cancers [12,15–21,23–30] . However, such conclusions remain controversial [8,17,22] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most importantly, AKIP1 is also a promising oncology-related factor in recent studies. For instance, AKIP1 is upregulated in several cancers, and it also correlates with more deteriorative tumor features and survival profiles in these cancer patients, which suggests that it participates in the progression of many cancers (15)(16)(17)(18)(19). Above all, there is also correlation between AKIP1 and gastric cancer, which elucidates that it is involved in tumor progression through the modulation of Slug-induced epithelial-mesenchymal transition, which then enhances growth and metastasis of the tumor (20).…”
Section: Introductionmentioning
confidence: 90%